Pemberdayaan Karyawan Sebagai Alternatif Membangun Keunggulan Kompetitif - Titiek Mulyaningsih (EBBANK, 2010)
The new paradigm of Human Resource Management put employees as working partner of the company instead of production factor of the company. As a working partner, employees have some added values compared to other production factors. These added values consist of feelings, creativity, and motivation. The empowerment of these added values would bring competitive advantages to the company.There are four main strategies in employee empowerment, which are; 1) Growing the consciousness, willingness and management commitment to implement employee empowerment strategies. The core activity of employee empowerment is sharing trust and authority with such risks and the result would not be instantly gained. 2) Developing organizational structure and instruments to support employee empowerment. 3) Developing supporting system to employee empowerment. 4) Developing Human Resource and Organization behavior as the subjects of empowerment.Employee empowerment is a strategy that runs as a process, so, it is needed to be understood that the result might come in a long period of time. Moreover, employees and management would experience error learning. Therefore, patience and understanding is needed.